ASSESSMENT OF THE WORK ENVIRONMENT OF FACULTY OF A MEDICAL COLLEGE IN PAKISTAN - Saeed, Abid; Butt, Zahid Ahmad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Extensive research is done on nursing work environments but less is known about the job conditions and environments of other health professionals. This study was aimed to fill this information gap by highlighting the factors affecting the work environment and stressors causing turnover of staff. Methods: A cross sectional study was conducted in Bolan Medical College Quetta for the assessment of working environment of the faculty from 22nd April to 22nd July 2012. All permanent teaching staff was included. A structured questionnaire was adopted from health sciences association of Alberta (HSSA), 2006 work Environment Survey. An observational check list for assessment of the physical environment /infrastructure and other general physical stuff was used. Results: The faculty members were not satisfied with the security and safety of their work place but were satisfied with salaries, employer, and management. Work teams and relationship between employees and employers were respectful with good communication. Majority found their work times stressful and opportunities for on job trainings and professional development, adequate tools, equipment and conditions were mostly lacking. Conclusions: The overall working environment is not that good and few areas need serious attention like: professional development, trainings, adequate equipment, and security. Keywords: Cross Sectional Study, Working Environment, Faculty